Zakat As Original Source of Revenue For Aceh - Syahbandir, Syahbandir; Efendi, Efendi; Mahfud, Mahfud (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2019)
Article 180 (1) letter D of Aceh Governance Act No. 11 of 2006 on the Aceh Government articulated that zakat is one of the Aceh Province, regencies, or citiesâ€™ original revenue sources. However, the legal basis of collecting zakat in Pidie, Bireuen and Lhokseumawe is very weak as it is only based on the Head of Regency or Mayor Regulation. This research aims to examine Islamic aspects of zakat collection in Pidie Regency, Bireuen Regency and Lhokseumawe City, and whether such collection has been in accordance with existing laws or not. This is normative legal research by examining the collection of zakat from Islamic aspects and existing laws in regard with the collection of zakat within such three regions. The research shows that Pidie Regency does not collect income zakat as it follows Madhhab al-ShÄfiÊ¿Ä« which does not recognize it. The collection of this kind of zakat in Bireuen and Lhokseumawe has been in accordance with existing laws.